Simple Diffusion as the Mechanism of Okadaic Acid Uptake by the Mussel Digestive Gland - Juan Blanco; Helena Martín; Carmen Mariño; Araceli E. Rossignoli (Toxins, 2019)
Okadaic acid (OA) and other toxins of the diarrheic shellfish poisoning (DSP) group are accumulated and transformed mainly in many bivalves, inside the digestive gland cells. In this work the absorption of okadaic acid by those cells has been studied by supplying the toxin dissolved in water and including it in oil droplets given to primary cell cultures, and by checking if the uptake is saturable and/or energy-dependent. Okadaic acid was found to be absorbed preferentially from the dissolved phase, and the uptake from oil droplets was substantially lower. The process did not require energy and was non-saturable, indicating that it involved a simple diffusion across the cellular membrane. Some apparent saturation was found due to the quick biotransformation of OA to 7-O-acyl esters.